Adab sebagai Jembatan antara Ilmu dan Amal dalam Pembentukan Karakter Siswa: Adab as a Bridge between Knowledge and Deeds in Shaping Students' Character - Muhammad Hamka; Budi Handrianto; Agusman, Agusman (Litera Academica Publishing, 2024)
The importance of adab in education is increasingly recognized amidst the moral and ethical challenges faced by today's young generation. Adab serves not only as a social norm but also as a foundation that bridges knowledge and deeds in shaping students' character. This article examines the role of adab in shaping students' character by integrating knowledge and actions through a literature review and qualitative analysis of relevant studies. Findings show that adab plays a crucial role in facilitating a deeper understanding of knowledge and the effective application of good deeds. Adab helps students appreciate knowledge and encourages them to apply it in beneficial actions for themselves and their surroundings. The conclusion of this study is that integrating adab into education can strengthen the relationship between knowledge and deeds, resulting in students with good character, broad knowledge, and righteous actions. The implications of these findings are the need for a more holistic educational approach, focusing on both knowledge transfer and the development of adab and character, to produce excellent and virtuous future generations.